Efeitos dos processamentos da soja sobre o desempenho de frangos de corte - Marilane das Dores Silva (2013)
Two experiments were conducted to evaluate the performance of broilers fed soybean, considering the weight gain (GPM), feed intake (CRM), feed conversion (CA), measured at seven, 21 and 38 days of age, and carcass yield (RCA), relative weight of pancreas (RPCA) and liver (RFCA) for carcass at 38 days. In the first experiment evaluated the performance of broilers fed four levels, 25, 50, 75 and 100% of soybean meal hydrolyzate (FSH), compared to birds fed diets based on soybean meal + degummed soybean ( FS + OS). The second experiment evaluated the performance of broilers fed FS + OS, poultry fat more soybean meal (FS + OV), extruded whole soybean (SE) and roasted whole soybean (ST). The design used in both experiments was completely randomized with six replications with 31 birds, with the first trial were made linear regression analysis for adjustment for answers. In the first trial was observed that the average feed consumption decreased to seven days old, as they include increased levels of FSH, but a 21 days root-square regression was observed in the CRM, and replacement levels of FSH, reaching the CRM maximum at 16% inclusion of FSH, decreasing the CRM after this level, one to 38 days inclusion levels of soybean meal hydrolyzate did not affect feed intake. The GPM birds in treatments with 25, 50, 75, 100% inclusion of soybean meal hydrolyzate at seven, 21 and 38 days was affected by inclusion levels had lower GPM compared to the control treatment. CA deteriorated at 21 days was increased as the inclusion of FSH. However, when analyzing the CA during one to seven and one to 38 days, no significant differences. No significant differences in RCA, RPCA and RFCA. In the second experiment, no significant differences in the CA of birds from one to seven days, however one to 21 to 38 days there was a worse CA FS + OV treatment and better treatment with ST. The CRM from one to seven days and one at 38 days was lower in the treatment with ST, however, within one to 21 days there was no significant difference between treatments. GPM treatment with FS + OS treatment was superior to the FO +OV and IF, which were similar between the treatment with ST showed less weight gain of one to 38 days. The RCA, RPCA and RFCA, no significant differences. It is concluded that FSH did not improve the performance of broilers from one to 38 days, and chicks fed with ST had lower performance when compared to treatments OV + FS, FS + OS, SE.